2015
DOI: 10.1159/000374002
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of miRNA and mRNAs in Lesioned Tissues of Graves' Disease

Abstract: Background and Aims: Abnormal microRNA (miRNA) expression is found in many diseases including autoimmune diseases. However, little is known about the role of miRNA regulation in Graves' disease (GD). Here, we simultaneously detected different expressions of miRNA and mRNAs in thyroid tissues via a high-throughput transcriptomics approach, known as microarray, in order to reveal the relationship between aberrant expression of miRNAs and mRNAs spectrum and GD. Methods: Totally 7 specimens of thyroid tissue from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Furthermore, we and other investigators have found that distinct AITDs phenotypes may even share common susceptibility genes [2,3]. In our another study, we found that the miRNA-target gene network might be involved in the pathogenesis of GD [4]. …”
Section: Introductionmentioning
confidence: 59%
“…Furthermore, we and other investigators have found that distinct AITDs phenotypes may even share common susceptibility genes [2,3]. In our another study, we found that the miRNA-target gene network might be involved in the pathogenesis of GD [4]. …”
Section: Introductionmentioning
confidence: 59%
“…The aberrant profile of miRNA expressions was proved to be a risk factor for GD [24], though the role of rs907091 has not been clearly illustrated. Recently, rs907091 was also referred to as an expression quantitative trait locus for IKZF3 in lymphoblastoid cell lines [25].…”
Section: Discussionmentioning
confidence: 99%
“…miR-197 was also lower in biopsy-proven nonalcoholic fatty liver (Celikbilek et al, 2014), primary biliary cirrhosis (Ninomiya et al, 2013), multiple sclerosis1 (Margareta Jernås et al, 2013), uterine leiomyoma (Ling et al, 2015a), type 2 diabetes (Zampetaki et al, 2010) and increased in placentas of preeclampsia (Choi et al, 2013), Graves' disease (Qin et al, 2015). Furthermore, miR-197, in hepatitis B virus infected patients, gradually decreased along with the severity of liver disease symptoms.…”
Section: Mir-197 In Othersmentioning
confidence: 99%